2019
DOI: 10.1124/mol.119.116913
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Activation and Modulation of the Concatemeric α1β2γ2L GABAA Receptor

Abstract: The two-state coagonist model has been successfully used to analyze and predict peak current responses of the g-aminobutyric acid type A (GABA A) receptor. The goal of the present study was to provide a model-based description of GABA A receptor activity under steady-state conditions after desensitization has occurred. We describe the derivation and properties of the cyclic three-state resting-active-desensitized (RAD) model. The relationship of the model to receptor behavior was tested using concatemeric a1b2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 54 publications
5
34
0
Order By: Relevance
“…Curve‐fitting yielded a K PS of 1.9 ± 1.5 μ mol/L, and a d PS of 0.11 ± 0.06 with the number of PS binding sites constrained to 1. These are similar to the values (3.5 μ mol/L and 0.054, respectively) reported recently for the concatemeric α 1 β 2 γ 2L GABA A receptor (Germann et al ). When N PS was held at 2, the fitted K PS was 1.0 ± 0.6 μ mol/L, and d PS 0.35 ± 0.07.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Curve‐fitting yielded a K PS of 1.9 ± 1.5 μ mol/L, and a d PS of 0.11 ± 0.06 with the number of PS binding sites constrained to 1. These are similar to the values (3.5 μ mol/L and 0.054, respectively) reported recently for the concatemeric α 1 β 2 γ 2L GABA A receptor (Germann et al ). When N PS was held at 2, the fitted K PS was 1.0 ± 0.6 μ mol/L, and d PS 0.35 ± 0.07.…”
Section: Resultssupporting
confidence: 92%
“…We next investigated receptor modulation by the endogenous steroid PS. Previous work has indicated that the steroid inhibits steady‐state activity by promoting entry to the desensitized state (Akk et al ; Eisenman et al ; Germann et al ). Receptors were activated by 1 mmol/L GABA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although entry of GABAARs into the desensitized state is commonly studied in the context of orthosteric agonists, allosteric modulators will also affect the occupancy of this state during synaptic inhibition. In the case of one negative allosteric modulator, pregnenolone sulfate, inhibition of GABAARs is caused by directly acting on the desensitized state, enabling either stabilisation or increased entry of GABAARs into this state [49][50][51][52] . However, given that entry into the desensitized state is thought to follow receptor activation 10,53 , it is also likely that drugs which do not act directly on the desensitized state will also alter its occupancy indirectly, as a consequence of effects on receptor kinetics.…”
Section: Allosteric Modulators Can Induce Desensitization-dependent Ltpmentioning
confidence: 99%